1982
DOI: 10.1111/j.1528-1157.1982.tb05082.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitatory Effects of Intermittent Photic Stimulation on Visual Cortical Kindling

Abstract: There are few reports on kindling preparation by daily electrical stimulation to the primary visual cortex. In our previous studies on cats, it was demonstrated that repeated stimulation to the primary visual cortex brought a similar progress in seizure development as in amygdaloid kindling, although it took more trials. In this study, we examined the effects of intermittent photic stimulation (IPS) (2.5 Hz) on the visual cortical kindling preparation to clarify more underlying mechanisms of photosensitivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Despite numerous methodological differences the present results parallel those reported by Baba (1982). In both studies, pairing of visual stimuli with the kindling stimulus decreased the number of stimulations needed to elicit a generalized seizure.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Despite numerous methodological differences the present results parallel those reported by Baba (1982). In both studies, pairing of visual stimuli with the kindling stimulus decreased the number of stimulations needed to elicit a generalized seizure.…”
Section: Discussionsupporting
confidence: 91%
“…However, comparison of the present effect of training condition on kindled AD durations with those of Baba (1982) is complicated by the differences in experimental designs. Baba (1982) reported longer AD durations for the group that had the IPS paired with visual cortex kindling as compared with the control group. In the present study, shorter AD durations were found in the discrimination groups.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Neocortical kindling is characterized by a higher threshold to elicit acute seizures, an unstable seizure development, and for its difficulty to induce a generalized convulsive seizure state (Majkowski et al, 1981; Okamoto, 1982). However, neocortical kindling has been described in the visual (Baba, 1982; Ono et al, 1981; Wada et al, 1989), somatosensory (Majkowski et al, 1981), motor (Fukushima et al, 1987), auditory (Valentine et al, 2004), and associative cortices of the cat (Nita et al, 2008a; Nita et al, 2008b). Kindling was also demonstrated in different species including frogs, mice, gerbils, rats, rabbits, cats, dogs, rhesus monkeys, and baboons (reviewed in (McNamara et al, 1980)).…”
Section: The Kindling Modelmentioning
confidence: 99%